Modelo de referência para a proteção do conhecimento gerado e aplicado no ambiente de uma universidade pública: um estudo de caso na UTFPR - Cherubini, Edivan (2009)
With the opening of the national economy from the beginning of the decade of 90, the expansion of the globalization and the increasing use of the technology, the speed of the changes and the necessity to innovate, require that the companies and universities assume as strategy the intellectual protection, participating actively in the technological and economic development of its organizations and the country. To adjust the required university structure is necessary to support the mapping of groups of skills, support structures, internalize the culture of knowledge protection and institutionalize mechanisms of transfer and licensing of technologies. The objective of this study was to delineate a model of structure of reference for the “Innovation Agencies” in public Institutions of Superior Education. The used methodology was study of case and participant comment in the Innovation Agency of the UTFPR, that is the responsible environment for the intellectual property in the institution. It wascarried through a documentary study in two international universities and four national ones. As result of the research was possible to raise and to point elements considered essential to the protection of the intellectual property, incentive to innovation and its transference for the society, that was called reference structure, as well as, the construction and proposal of an organizational structure for the Innovation Agency of the UTFPR.